FRI0731-HPR Switch management between similar biological medicines, a communication information guide for nurses. (12th June 2018) - Voorneveld-Nieuwenhuis, J.E.; Moortgat, L.; Pavic Nikolic, M.; Crombez, P.; Oomen, B.; ,
Abstract : Background: Biologics are used in the field of rheumatology but are also important in other fields such as oncology and gastroenterology. Over the last few years, biosimilar versions of many biologicals have been launched. Patients may be switched depending on local rules and appointments. To provide support and information for nurses working with patients who are switching between similar biological medicines ESNO has taken the initiative to develop an information guide for nurses. Nurses can take the lead in implementing the transition between branded and biosimilar biologic medicines. This includes managing the process before, during and after the switch. Objectives: The guide was developed to provide support and information for nurses working with patients who are switching between similar biological medicines The guide provides examples of projects and best practices based on different specialties to increase trust in biological medicines including biosimilars. Its aim is to contribute to the safe use of and trust in biologic medicines, and give nurses the tools to implement switching decisions in a clinical context and deal with patient concerns, drawing on the learnings from real-life experiences. Methods: We collected previous experiences from nurses with switching biologics. We also developed a roadmap for how to inform patients, a set of frequently asked questions (FAQ) and points to consider when switching. Results: The guide is written in English and will be translated into the 23 different languages of the EU. With information about: - The definitions of biological and biosimilar medicines. · Switching and substitution. · The benefits of biosimilars · The nurses role in managing the exchange between similar biological medicine. The document also includes flow charts for switch implementation, follow up and support. Conclusions: Switching between similar biologicals opened new chapter in which nurses play a crucial role in communicating with patients and providing support and reassurance, before, during and particularly after the switch. This is build on nurses' many years of education, and their experience with patients in different situations. It is a process that requires time, patience and care. Patients may be concerned about changes in biologic medicines, and will have a lot of questions. Positive language is important in answering these questions, to provide confidence and reassurance. Patients need to know that their healthcare professionals understand the reasoning behind the change and are confident that it is the right thing to do. To avoid confusion, the team of nurses and other healthcare professionals should have a consistent explanation that is used by all. References: 1. European Commission. What I need to know about biosimilar medicines: Information for patients2016. 2. European Medicines Agency and European Commission. Biosimilars in the EU: Information guide for healthcare professionals2017. 3. Read C. Specialist nurses support cost effective drugs for treatment. HSJ2017. Disclosure of Interest: J. Voorneveld-Nieuwenhuis: None declared, L. Moortgat: None declared, M. Pavic Nikolic: None declared, P. Crombez: None declared, B. Oomen Grant/research support from: This document has been created with funding from Medicines for Europe and EFPIA.